Influence of Geometry-Induced Frequency Dispersion on the Impedance of Ring Electrodes. (1st May 2017) - Chen, Yu-Min; Alexander, Christopher L.; Cleveland, Christopher; Orazem, Mark E.
Abstract : Highlights: Finite-element simulations of the impedance of ring electrodes. Characteristic dimensions for ring electrodes identified Characteristic frequencies found at which ring electrodes cause time-constant dispersion Abstract: Finite-element simulations for the impedance response of ring electrodes were used to identify the characteristic frequency associated with the influence of electrode geometry on impedance response. An approximate expression for the characteristic ring-electrode dimension was found to be adequate for a wide ring, and have an error of 20 percent for a thin ring. A refined expression for the characteristic dimension is presented. The characteristic frequency associated with the influence of ring-electrode geometry is always larger than that associated with the geometry of a disk. These results guide the design of ring-shaped sensors that employ impedance measurements.